1985
DOI: 10.1016/s0022-5347(17)47663-4
|View full text |Cite
|
Sign up to set email alerts
|

Dichloromethylene-Diphosphonate in Patients with Prostatic Carcinoma Metastatic to the Skeleton

Abstract: A total of 17 patients with multiple osteoblastic bone metastases owing to prostatic carcinoma was treated with 2-dichloromethylene-diphosphonate, a powerful inhibitor of bone resorption. The drug was given intravenously (300 mg.) for 2 weeks and then orally (3,200 mg.) or intramuscularly (100 mg.) for 4 to 11 weeks. A definite improvement in pain, assessed by daily consumption of analgesic drugs and by an analogic scale, was observed within 10 days in 16 of the 17 patients. Four patients confined to bed rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(37 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…While NBPs act inside cells, inhibiting the mevalonate cycle, nonNBPs act by promoting direct cytotoxicity towards osteoclasts and osteoblasts, thereby inducing apoptosis and inhibiting the ATP/ADP translocase enzyme. 13,14 The differences in pharmacological action between the groups determine their effects on the inflammatory process. Non-NBPs such as clodronate have anti-inflammatory action and antirheumatic activity, whereas this is not well established in NBPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While NBPs act inside cells, inhibiting the mevalonate cycle, nonNBPs act by promoting direct cytotoxicity towards osteoclasts and osteoblasts, thereby inducing apoptosis and inhibiting the ATP/ADP translocase enzyme. 13,14 The differences in pharmacological action between the groups determine their effects on the inflammatory process. Non-NBPs such as clodronate have anti-inflammatory action and antirheumatic activity, whereas this is not well established in NBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Non-NBPs such as clodronate have anti-inflammatory action and antirheumatic activity, whereas this is not well established in NBPs. 14 Preclinical studies have demonstrated that osteolytic lesions always precede the abnormal bone deposition (osteoblastosis) that gives the osteoblastic appearance to the majority of metastatic skeletal lesions from prostate cancer. 7 It has been shown through biopsies of metastatic skeletal lesions that excessive bone absorption occurs at these sites, in the same way as it occurs in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in skeletal morbidity was usually reported. There were initially rather fewer studies in the prostate cancer setting, although some early work showed reductions in bone pain with clodronate, 43,44 although this was not later borne out in randomised studies with this drug. 45,46 Early small-scale studies with pamidronate provided encouraging signs of its potential benefit, 47,48 but it was several years before a well-designed randomised study was published on the use of later-generation bisphosphonates in prostate cancer.…”
Section: Current Treatment Options For Bone Metastasesmentioning
confidence: 99%
“…Only two of the limited number of studies on treatment of painful bone metastases due to prostate cancer with clodronate (Adami et al, 1985;Adami et al, 1989;Elomaa et al, 1992;Vorreuther et al, 1992;Vorreuther, 1993;Kylmala et al, 1994;Cresswell et al, 1995) have been placebo controlled (Adami et al, 1989;Elomaa et al, 1992). Adami and colleagues (1989) first showed, in 13 patients, that intravenous administration of clodronate was more effective in reducing bone pain than oral administration and that the effect lasted longer when intravenous administration was followed by oral treatment.…”
mentioning
confidence: 99%